The Impact of Quadrivalent Human Papillomavirus (HPV; Types 6, 11, 16, and 18) L1 Virus-Like Particle Vaccine on Infection and Disease Due to Oncogenic Nonvaccine HPV Types in Sexually Active Women Aged 16–26 Years - Wheeler, Cosette M.; Kjaer, Susanne K.; Sigurdsson, Kristján; Iversen, Ole-Erik; Hernandez-Avila, Mauricio; Perez, Gonzalo; Brown, Darron R.; Koutsky, Laura A.; Tay, Eng Hseon; García, Patricia; Ault, Kevin A.; Garland, Suzanne M.; et al. (The Journal of infectious diseases, 2009)
BackgroundWe evaluated the impact of a quadrivalent human papillomavirus (HPV) vaccine on infection and cervical disease related to 10 nonvaccine HPV types (31, 33, 35, 39, 45, 51, 52, 56, 58, and 59) associated with >20% of cervical cancers. The population evaluated included HPV-naive women and women with preexisting HPV infection and/or HPV-related disease at enrollment MethodsPhase 3 efficacy studies enrolled 17,622 women aged 16–26 years. Subjects underwent cervicovaginal sampling and Pap testing on day 1 and then at 6–12-month intervals for up to 4 years. HPV typing was performed on samples from enrollment and follow-up visits, including samples obtained for diagnosis or treatment of HPV-related disease. All subjects who received ⩾1 dose and returned for follow-up were included ResultsVaccination reduced the rate of HPV-31/33/45/52/58 infection by 17.7% (95% confidence interval [CI], 5.1% to 28.7%) and of cervical intraepithelial neoplasia (CIN) 1–3 or adenocarcinoma in situ (AIS) by 18.8% (95% CI, 7.4% to 28.9%). Vaccination also reduced the rate of HPV-31/58/59–related CIN1–3/AIS by 26.0% (95% CI, 6.7% to 41.4%), 28.1% (95% CI, 5.3% to 45.6%), and 37.6% (95% CI, 6.0% to 59.1%), respectively. Although a modest reduction in HPV-31/33/45/52/58–related CIN2 or worse was observed, the estimated reduction was not statistically significant ConclusionsThese cross-protection results complement the vaccine’s prophylactic efficacy against disease associated with HPV-6, -11, -16, and -18. Long-term monitoring of vaccinated populations are needed to fully ascertain the population-based impact and public health significance of these findings Trial registrationClinicalTrials.gov identifiers: NCT00092521, NCT00092534, and NCT00092482